KAIDAH-KAIDAH FONOLOGI BAHASA SUMBA DIALEK KAMBERA - Editor Team (Jurnal Lazuardi, 2019)
This study aims to address problems related to morpheme structure requirements and phonological processes and rules. The Kambera dialect (BSDK) has 24 origin segments consisting of nineteen consonant segments, namely / p, b, t, d, k, m, n, ŋ, ň, mb, nd, nj, ŋg, j, h , l, r, w, y /, and five vocal segments, i.e., u, e, o, a /. Phonetically, four vocal segments of them experience relaxation, such as / i, u, e, o / being [I, U, E, O]. To distinguish the twenty-four segments, fourteen distinguishing features are needed. The segment (segment) found in BSDK is very limited, there are only vocal groups, whereas consonant groups are not found. To explain the possibility of existing vocal groups, a rule has been formulated, that is, if - then. Vocal groups in BSDK include / i - u /, / i - a /, / u - a /, / u - i /, / e - u /, / e - i /, / o - i /, / a - i /, and / a - u /. To describe the phonological process that occurs, four phonological rules are needed, namely (1) vocal and semivocal insertion rules, (2) syllable repetition rules, and (3) vocal relaxation rules, and (4) vocal change rules.